Simultaneous registration of gnomonic projections and central perspectives. (September 2014) - Barazzetti, Luigi; Previtali, Mattia; Scaioni, Marco
Abstract An innovative methodology that combines central perspectives and panoramic gnomonic projections into an integrated bundle block adjustment is discussed. The use of both kinds of images generates metric products with a superior level of detail (image resolution) compared with conventional central perspectives alone, whilst achieving the accuracy of the latter. The entire methodology is intended as a low‐cost solution to improving the ground sampling distance over that achievable with single exposures by conventional modern terrestrial cameras. Very high‐resolution close‐range images can be automatically generated and oriented with a rigorous multi‐step procedure that integrates both types of images within a unified least squares adjustment. The advantages and disadvantages of the proposed approach are analysed from both theoretical and practical points of view and illustrated through a series of examples.